Lietuvos komunistų partijos pirmoji „Spartako“ spaustuvė (1920.IX–1922.III.28) - Žeimantas, Viktoras (Knygotyra, 1972)
The article is based on the analysis of technical means of the Spartakas I press. The Lithuanian Communist Party had some printing presses named Spartakas, thus they are numbered in order to distinguish them. All the known archival material, the reminiscencies of Nora Melnalskaite, who worked at this press, and also the memoirs of the authors who wrote about the work of the Party and its press in this period, have been used in the present work. It has been established that the secret press carried out its first work in September, 1920. The day when the bourgeois secret police discovered Spartakas I is the date of its closing. It happened on the 28th of March, 1922. Spartakas I was one of the greatest illegal enterprises of the Lithuanian Communist Party during all its secret activities. The press disposed not only of relief printing but also of planographic printing (lithography). Spartakas I printed the newspapers Tiesa (“Truth”) Oct. 1920 to 28th Feb. 1922, Kareivių tiesa (“Soldiers’ Truth”) 8th March, 1920, to 3rd Jan., 1922. Jaunasis Komunistas (“The Young Communist”) Apr. 1921 to Feb. 1922, Czervony sztandar (“The Red Flag”) 1921, Борьба (“Struggle”) Nov. 1920 to 7th March, 1922, and the appeals in Lithuanian, Russian, Polish and Jewish.